2021
DOI: 10.24198/jaab.v4i1.31998
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tax Fairness, Tax Socialization and Tax Understanding on Tax Compliance: A Study on Micro, Small and Medium Enterprises (MSMEs)

Abstract: This research aims to identify the effect of fairness, socialization, and understanding on the Micro Small Medium Enterprises (MSMEs) taxpayer compliance towards Government Regulation number 23/2018 regarding income tax from business received or accrued by taxpayers who have certain gross turnover. This research used a quantitative approach, and data were collected using the Likert scale questionnaire. In this research, the population was 283 SME actors registered at the Cooperatives and Small and Medium Enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
0
9
0
8
Order By: Relevance
“…With the tax leisure policy during the COVID-19 pandemic observed that appreciation of guidelines and the benefits obtained from the tax rest policy impacted taxpayer compliance in reporting Article 21 Income Tax Returns. Alm et al (2020), located tax compliance via the usage of a behavioural approach that attitudes toward behaving, subjective norms and behavioral manage affect taxpayer compliance (Lestary and Yudianto, 2021;Saad and Abdullah, 2014). The taxation socialisation and understanding of taxation positively affect SMEs taxpayers' compliance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the tax leisure policy during the COVID-19 pandemic observed that appreciation of guidelines and the benefits obtained from the tax rest policy impacted taxpayer compliance in reporting Article 21 Income Tax Returns. Alm et al (2020), located tax compliance via the usage of a behavioural approach that attitudes toward behaving, subjective norms and behavioral manage affect taxpayer compliance (Lestary and Yudianto, 2021;Saad and Abdullah, 2014). The taxation socialisation and understanding of taxation positively affect SMEs taxpayers' compliance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Theory of Planned of Behavior (TPB) khususnya normative belief yang menjelaksan bahwa seseorang akan melakukan suatu jika perilakunya diterima bagi orang-orang yang dianggap penting pada kehidupannya dan dapat menerima hal tersebut. Dalam situasi tersebut seorang wajib pajak memiliki dukungan serta mptivasi dalam pemenuhan kewajiban pelaporan pajaknya (Nadiani dan Setiawan, 2019) Berdasarkan penelitian yang dilakukan oleh (Lestary & Yudianto, 2021) dan (Machfuzhoh, 2021) menjelaskan tentang sosialisasi pajak memiliki pengaruh positif dan signifikan pada kepatuhan wajib pajaknya. Penelitian serupa dari (Darmanto, 2018) serta (Muhamad et al, 2020) Hal tersebut didukung oleh penelitian (Fitria & Supriyono, 2019) menyatakan bahwa insentif pajak memiliki pengaruh positif pada kepatuhan WP UMKM.…”
Section: Pendahuluanunclassified
“…Maka, sosialisasi pajak berpengaruh secara positif terhadap kepatuhan wajib pajak UMKM di Kabupaten Gianyar. Hasil ini sesuai dengan penelitian (Lestary & Yudianto, 2021) dan (Machfuzhoh, 2021) serta penelitian (Darmanto, 2018) dan (Muhamad et al, 2020) serta penelitian (Andrew & Sari, 2021) yang menyebutkan sosialisasi pajak memiliki pengaruh posittif pada tingkat kepatuhan wajib pajaknya.…”
Section: Tabel 7 Hasil Uji Heterokedastisitasunclassified
“…In his consideration, this Government Regulation was made to encourage the public to participate in formal economic activities, by providing convenience and more justice to taxpayers. In addition, MSME actors who have not previously registered and reported their business results can be encouraged to register and start paying taxes on their business results as a form of contribution to the state (Lestary et al, 2021).…”
Section: Introductionmentioning
confidence: 99%